Analisa kerusakan bearing mesin kompresor sekrup boge tipe bs 102 nr 1023728 - Muhammad Nazri Ramali; Tomi Abdilah; Irwan Suyadi (FAKULTAS SAINS DAN TEKNOLOGI - UTND, 2023)
A compressor is a machine for compressing air or gas. Air compressors usually suck airfrom the atmosphere. However, there are also those who suck in air or gas at a pressurehigher than atmospheric pressure. In this case the compressor works as a booster. On theother hand, there are also compressors that suck in gas at a lower pressure than atmosphericpressure. One of the problems with screw type compressor machines is overload, where thepower required by the compressor is less than the normal requirement, which forces themachine to work more than its capacity limits. In the end, this results in the electric motorgetting hotter (overheating) and can even cause a fire in the magnetic winding. The aim ofthis research is to analyze the causes of bearing damage to the Boge type BS 102 screwcompressor machine outside the maintenance schedule which disrupts the productionprocess. This research used field observation methods, reviewing machine manuals andliterature studies. The results of the research show that the cause of damage to bearings inbogie screw compressor machines is due to an incorrect lubrication system and installationand repair of bearings that do not comply with procedures